Topoisomerase activity is associated with purified SV40 T antigen. - Mann, K (1993)
Purified SV40 T antigen has been assayed for topoisomerase activity. The ability to relax negatively-supercoiled SV40 DNA was found in preparations of T antigen purified either from human 293 cells infected with Ad5-SVR111 virus or from insect Sf9 cells infected with recombinant baculovirus 941T. The T antigen-associated relaxing activity was stimulated by MgCl2 and was not dependent on ATP, suggesting that it is not due to cellular topoisomerase II. The topoisomerase activity was immunoprecipitated by a monoclonal antibody specific for T antigen, but not by a control monoclonal antibody. In addition, immunoblotting of purified T antigen from human 293 cells with antihuman topoisomerase I and anti-human topoisomerase II antibodies failed to detect cellular topoisomerases I or II. Sedimentation analysis of purified T antigen revealed that the topoisomerase activity co-sedimented with the hexameric form of T antigen at 23S. The topoisomerase activity is, therefore, either inherent to T antigen or due to a cellular topoisomerase I tightly bound to, and co-purifying with, T antigen.